Evaluation of odontometric methods in immature permanent teeth: research for a better practice - Vicko, Kristina; Nikolic Ivosevic, Jelena; Petrovic, Bojan (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Determination of correct working length is one of the keys to success in root canal treatment. It provides efficient canal cleaning and shaping, a three-dimensional chermetic obturation and an optimal healing procees following root apex formation. The aim of this work was to evaluate and compare the accuracy and applicability of working lengths determined in permanent immature teeth in vivo using different clinical methods. Methods. The research was conducted at the Dental Clinic of Vojvodina in Novi Sad, the Department of Pediatric and Preventive Dentistry. A sample of 30 canals of young permanent teeth were selected for the research. Inclusion criteria were: a need for endodontic treatmant, young permanent teeth, teeth with incomplete apex formation according to Demirijans stages F and G determined on radiography. Exclusion criteria: more than 3 years from eruption, pathological and iatrogenic resorption of the apex. The canal lenght was measured first on the initial radiograph used later as the parameter for comparison with various clinical methods. Results. The greatest average difference of measured working lengths was found by using electroodontometry and the paper point method afterwards. Regarding individual measurements, the most unprecise reading was with electroodontometry and tactile method up to 5 mm difference, and 4.6 mm was the maximal deviation for radiographic method. A deviation was defined by matching the measurements with a canal length measured on the initial radiograph. Our results showed that there was a difference between observed methods, although there was no statistical significance. Conclusion. The radiographic method and tactile method stand out as dominant methods for odontometry in permanent immature teeth, thanks to highly accurate readings, while the electroodontometry is considered the most unreliable method for determining working length in immature permanent teeth.
Keywords: endodontics; root canal preparation; odontometry